The effect of Imatinib Mesylate in diffuse-type Tenosynovial Giant Cell Tumours on MR imaging and PET-CT. (December 2020) - Mastboom, M.J.L.; Lips, W.; van Langevelde, K.; Mifsud, M.; Ng, C.; McCarthy, C.L.; Athanasou, N.A.; Gibbons, C.L.M.H.; van de Sande, M.A.J.
Abstract: Introduction: Recurrence rates remain high after surgical treatment of diffuse-type Tenosynovial Giant Cell Tumour (TGCT). Imatinib Mesylate (IM) blocks Colony Stimulating Factor1 Receptor (CSF1R), the driver mechanism in TGCT. The aim of this study was to determine if IM reduces the tumour metabolic activity evaluated by PET-CT and to compare this response with the response seen on MR imaging. Materials and methods: 25 Consecutive patients treated with IM (off label use) for locally advanced (N = 12) or recurrent (N = 13) diffuse-type TGCT were included, 15 male and median age at diagnosis 39 (IQR 31–47) years. The knee was most frequently affected (n = 16; 64%). The effect of IM was assessed pre- and post-IM treatment by comparing MR scans and PET-CT. MR scans were assessed by Tumour Volume Score (TVS), an estimation of the tumour volume as a percentage of the total synovial cavity. PET-CT scans were evaluated based on maximum standardized uptake value (SUV-max). Partial response was defined as more than 50% tumour reduction with TVS and a decrease of at least 30% on SUV-max. Results: Median duration of IM treatment was 7.0 (IQR 4.2–11.5) months. Twenty patients (80%) discontinued IM treatment for poor response or intended surgery. Twenty patients experienced an adverse event grade 1–2, three patients grade 3 (creatinine increment, neutropenic sepsis, liver dysfunction). MR assessment of all joints showed 32% (6/19) partial response and 63% (12/19) stable disease, with a mean difference of 12% (P = 0.467; CI -22.4-46.0) TVS between pre- and post-IM and a significant mean difference of 23% (P = 0.021; CI 4.2–21.6) in all knee lesions. PET-CT, all joints, showed a significantly decreased mean difference of 5.3 (P = 0.004; CI 1.9–8.7) SUV-max between pre- and post-IM treatment (58% (11/19) partial response, 37% (7/19) stable disease). No correlation between MR imaging and PET-CT could be appreciated in 15 patients with complete radiological data. Conclusion: This study confirms the moderate radiological response of IM in diffuse-type TGCT. PET-CT is a valuable additional diagnostic tool to quantify response to tyrosine kinase inhibitor treatment. Its value should be assessed further to validate its efficacy in the objective measurement of biological response in targeted systemic treatment of TGCT. Highlights: Tenosynovial Giant Cell Tumour (TGCT), is a rare mono-articular tumour affecting the synovium, bursae and tendon sheath. Diagnosing and staging the extension of TGCT is assessed on MR imaging and can be quantified by the Tumour Volume Score (TVS). PET-CT provides understanding of the metabolic activity of TGCT, expressed as maximum Standardized Uptake Values (SUV-max). As treatment in diffuse-type TGCT, Imatinib Mesylate, a tyrosine kinase inhibitor, can be provided. PET-CT is a valuable additional diagnostic tool to quantify response to tyrosine kinase inhibitor treatment in TGCT.